Cannabinoid Receptor 1 Blockade Attenuates Obesity and Adipose Tissue Type 1 Inflammation Through miR-30e-5p Regulation of Delta-Like-4 in Macrophages and Consequently Downregulation of Th1 Cells - Miranda, Kathryn; Mehrpouya-Bahrami, Pegah; Nagarkatti, Prakash S.; Nagarkatti, Mitzi (Frontiers in Immunology, 2019)
Obesity is characterized by chronic low-grade inflammation that contributes to development of cardiometabolic disorders. Cannabinoid receptor 1 (CB1) antagonists attenuate diet-induced obesity (DIO) and related inflammation, although the precise anti-inflammatory mechanisms involved have not been fully explored. In the current study we used a mouse model of DIO intervention to determine the microRNA (miRNA, miR)-mediated anti-obesity and anti-inflammatory effects of the CB1 antagonist, AM251. DIO mice that were fed high-fat diet (HFD) for 12 weeks were treated with AM251 (10mg/kg) for an additional four weeks. HFD+AM251 mice experienced rapid and prolonged weight loss and reduced inflammatory M1 adipose tissue macrophage (ATM) infiltration. To investigate miRNA-mediated regulation of ATMs, F4/80+ cells from stromal vascular fractions of epididymal fat were subjected to miR microarray analysis. Several miRs were differentially expressed in AM251-treated mice that were independent of calorie restriction. Prominently, miR-30e-5p was upregulated in ATMs from HFD+AM251 mice while the miR-30e-5p target, DLL4, was downregulated. Consistent with a decrease in DLL4-Notch signaling, fat storage and pro-inflammatory cytokine/chemokine expression was reduced following AM251 treatment. Furthermore, we found that AM251-treated macrophages can suppress DLL4-mediated Th1 polarization in CD4+ T cells. Together these data demonstrate that blocking CB1 receptors leads to upregulation of miR-30e-5p and down regulation of DLL4 in ATMs, which in turn suppress DLL4-Notch signaling-induced polarization of inflammatory Th1 cells and adipocyte energy storage. This combined effect of ATMs and T cells leads to an anti-inflammatory state and attenuation of diet-induced obesity. These data support therapeutic potential of miR-30 in the treatment of cardiometabolic disorders.